FGF14‐related episodic ataxia: delineating the phenotype of Episodic Ataxia type 9. Issue 4 (12th March 2020) - Piarroux, Julie; Riant, Florence; Humbertclaude, Véronique; Remerand, Ganaelle; Hadjadj, Jessica; Rejou, Franck; Coubes, Christine; Pinson, Lucile; Meyer, Pierre; Roubertie, Agathe
Abstract: We report four patients from two families who presented attacks of childhood‐onset episodic ataxia associated with pathogenic mutations in the FGF14 gene. Attacks were triggered by fever, lasted several days, and had variable frequencies. Nystagmus and/or postural tremor and/or learning disabilities were noticed in individuals harboring FGF14 mutation with or without episodic ataxia. These cases and literature data delineate the FGF14‐ mutation‐related episodic ataxia phenotype: wide range of age at onset (from childhood to adulthood), variable durations and frequencies, triggering factors including fever, and association to chronic symptoms. We propose to add FGF14 ‐related episodic ataxia to the list of primary episodic ataxia as Episodic Ataxia type 9.